영한사전 대응어 오류의 역사적 고찰 - 송은하(Song, Eunha); 정영국(Jeong, Young-kuk) (한국사전학, 2014)
There have been a couple of studies focusing on inappropriate or inaccurateequivalents in English-Korean dictionaries since the early 2000s. These studies,however, do not touch on the historical aspects of the appearance of these errors inchronologically different dictionaries. The main purpose of this study is, therefore,to trace the origins of inappropriate equivalents in current English-Koreandictionaries. To meet this aim, 6 headwords, which include equivalent errors incurrent English-Korean dictionaries, were selected to analyze. The 7English-Korean dictionaries, published from 1890 to 1960, and 3 English-Englishdictionaries, published from 1895 to 1957, were consulted to compare the meaningof each word. It was found out that most of the equivalent errors first began toappear in the dictionaries published after Korean liberation. According to thefindings, this study surmises that most equivalent errors occurred after 1945 arosefrom the sudden increase of the number of headwords and the length of entries inEnglish-Korean dictionaries. KCI Citation Count: 0